Gender Gap in Entrepreneurial Potential in Finland and Reflecting Its Underlying Causes - Saarela, Martti; Björk, Pauliina; Kotavaara, Ossi; Muhos, Matti; Heikkinen, Mervi (Umeå University Library, 2024)
The gender gap in entrepreneurship is a widely recognized phenomenon meaning that women are less likely to start a business than men. However, increased gender equality is believed to remove barriers to female entrepreneurship. We used secondary data collected for Global Entrepreneurship Monitor from 2003, 2009, 2015, and 2021 to get closer to this phenomenon in Finland, one of the most equal countries in the world. The aim of the study was to clarify the gender gap in entrepreneurship potential in Finland during recent decades, taking into account different age groups. We found that the gender gap exists in business start-up intentions and has not narrowed in the twenty-first century in any age group. A clear gender gap was also found in fear of failure in starting a business and perceived skills in entrepreneurship. Finally, the underlying causes of the gender gap in the Finnish context are discussed.